Lack of Adrenomedullin Aggravates Acute TNBS-Induced Colitis Symptoms in Mice, Especially in Females - Martínez-Herrero, Sonia; Larrayoz, Ignacio M.; Narro-Íñiguez, Judit; Rubio-Mediavilla, Susana; Martínez, Alfredo (Frontiers in Physiology, 2017)
Adrenomedullin (AM) is a biologically active peptide which has been tested as a new therapy for inflammatory bowel disease (IBD) in animal models and in patients with severe ulcerative colitis. We used an inducible knockout (KO) mouse model for AM to evaluate the effects of endogenous levels of this peptide on the development and degree of pathogenesis of IBD. Acute colitis was induced in mice of both sexes by rectal instillation of 3 mg 2,4,6-trinitrobenzenesulfonic acid (TNBS) in 100 µL of 50% ethanol. Control mice received the same volume of saline in 50% ethanol. During the following 5 days, the weight and the disease severity index of all animals were recorded. After sacrifice, the inflammatory response was macroscopically assessed by analyzing the weight of the colon; by histomorphometrical analysis on histological sections; and by qRT-PCR determination of different inflammatory, adhesion, and regeneration molecules. TNBS administration caused a significantly more severe colitis in KO mice, and especially in females, when compared to wild type (WT) animals. Abrogation of the AM gene caused more severe diarrhea, accompanied by rectal bleeding, anorexia, and a significant increase of colon weight. Histological analysis of TNBS-treated KO mice showed large areas of lymphocyte infiltrates in the mucosa and submucosa, with loss of tissue architecture. No alterations were observed in the expression levels of inflammatory cytokines at the time of sacrifice; meanwhile lack of AM resulted in lower levels of some adhesion molecules and regeneration markers. Taken together, these results support the protective role of endogenous AM against the development of acute colitis, and that its effects are particularly beneficial on females.